1999
DOI: 10.1590/s0004-27301999000300003
|View full text |Cite
|
Sign up to set email alerts
|

Fatores hormonais e genéticos na próstata normal e neoplásica

Abstract: Recently, a great deal of attention has focused on the growth regulatory effects of androgens in prostate cells. This has also resulted in much interest in the role of these steroid hormones in the development and maintenance of both normal and neoplastic prostate. However, it has not been possible to identify the exact relationship between androgenic hormone levels and the risk of this disease. The hormone-androgen receptor complex, by association with the DNA androgen response elements, specifically promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
4
0
4
Order By: Relevance
“…Androgen hormones are considered important regulators of the processes of development, maturation, homeostasis, and functioning of the prostate gland (Carvalho‐Salles & Tajara, 1999; Taboga et al, 2009), being essential for the initiation of secretory activity during puberty (Campos, 2014), as well as the maintenance of morphology, functioning, and control of the mechanisms of cell proliferation and death in adults (Marker et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Androgen hormones are considered important regulators of the processes of development, maturation, homeostasis, and functioning of the prostate gland (Carvalho‐Salles & Tajara, 1999; Taboga et al, 2009), being essential for the initiation of secretory activity during puberty (Campos, 2014), as well as the maintenance of morphology, functioning, and control of the mechanisms of cell proliferation and death in adults (Marker et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Spearman correlation testing showed that the photoperiod was directly correlated to both temperature and rainfall in the analyzed region. This indicates that all abiotic factors were synergized to provide an increased food supply during the rainy season (fruits), which provides a more favorable environment for reproduction for a fru- -Salles & Tajara, 1999;Taboga et al, 2009), being essential for the initiation of secretory activity during puberty (Campos, 2014), as well as the maintenance of morphology, functioning, and control of the mechanisms of cell proliferation and death in adults (Marker et al, 2003).…”
Section: Ventral Prostatementioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, esse hormônio também é produzido pelas suprarrenais que, sob influência do hormônio adrenocorticotrófico (ACTH) liberado pela hipófise, são induzidas a secretar androstenediona, que é convertida em testosterona perifericamente. Assim que é liberada no sangue, a testosterona se a liga proteínas, com uma pequena quantidade permanecendo livre (CARVALHO-SALLES & TAJARA, 1999;TABOGA et al, 2009). A testosterona livre e, portanto, ativa, adentra a célula prostática através de difusão simples pela membrana até chegar ao citoplasma, onde é convertida pela enzima 5-alfarredutase em dihidrotestosterona (DHT).…”
Section: Introductionunclassified
“…Além dos andrógenos, outros fatores também podem atuar na morfologia e fisiologia da próstata, como os estrógenos, o hormônio do crescimento, a prolactina, a insulina e fatores produzidos pelas próprias células prostáticas, os quais participam de processos autócrinos, parácrinos ou intrácrinos (CARVALHO-SALLES & TAJARA, 1999). Dessa forma, pode-se afirmar que a próstata é influenciada por fatores extrínsecos (orgânicos, hormonais, alimentares, imunológicos etc.)…”
Section: Introductionunclassified